Evaluation of haematological and biochemical changes in plasmodium berghei-infected mice treated with leaf extract of cassia sieberiana and chromolaena odorata - Nworgu, Confidence Ogechi; Mandah, Patience Chitu (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
The haematological and Biochemical effect of Cassia sieberiana and Chromolaena odorata leaf extract on mice infected with Plasmodium berghei was evaluated. 30 Swiss albino mice (23-32g) were divided into 6 groups of five per group. Groups PC, CC1, CC2, CC3, and CC4 were infected with blood containing the parasite. Group NC was not infected and served as the normal control. On the 5th day after infection, the mice in each group were treated. Mice in Groups CC2, CC3 and CC4 were administered orally with 250, 500 and 1000 mg/kg body weight of Cassia sieberiana and Chromolaena odorata leaf respectively for five days. Group PC was not treated while Group NC was given distilled water. Group CC1 was treated with 10 mg/kg body weight of chloroquine. After treatment, these mice were sacrificed and blood samples were collected for haematological and biochemical analysis. The result of the combined leaf extract on the haematological parameter indicated that packed cell volume, haemoglobin and red blood cell, were significantly increased by the extract in a dose-dependent mode, while White blood cell, monocytes, neutrophils and lymphocytes were significantly (p<0.05) reduced by the extract in a dose-dependent manner when compared to the parasitized untreated group. The level of aspertate transferase, alanine transferase, total protein concentration, urea and creatinine, alkaline phosphate and total bilirubin in all the mice infected with the parasite significantly (p < 0.05) increased. However, on the administration of the extract it was reduced in the treated groups. The reduction in the levels of these enzymes is an indication that Cassia sieberiana and Chromolaena odorata have no hepatotoxic effect on the mice at the dose levels administered.